Breast Reconstruction for Medicaid Beneficiaries: A Systematic Review of the Current Evidence. Issue 2 (3rd March 2020) - Siotos, Charalampos; Azizi, Armina; Assam, Larissa; Rosson, Gedge D.; Seal, Stella M.; Pollack, Craig E.; Aliu, Oluseyi
Abstract: Introduction: Medicaid beneficiaries are a generally disadvantaged population with access to elective specialty services. We sought to better understand utilization of breast reconstruction by Medicaid beneficiaries. Methods: We systematically searched PubMed, Scopus, Web of Science, and CINAHL databases for studies comparing breast reconstruction rates by insurance type. We extracted the information of interest to qualitatively and quantitatively synthesize the results of the studies. Results: We identified seven eligible studies. Overall, the rates of breast reconstruction have increased across insurance groups. However, our results show that Medicaid beneficiaries were on average less likely to receive breast reconstruction in comparison to patients with private insurance. Although, Medicaid patients again were more likely to receive breast reconstruction in comparison to Medicare beneficiaries. Conclusion: There is wide disparity in reconstruction rates by insurance status. However, with continued increase in the adult Medicaid population due to widening eligibility expansion, disparities involving this vulnerable population should be examined for causes and solutions.